(untitled) (The Pakistan Development Review, 2025)
Dividend of our much-touted youth bulge will remain a pipedream unless our policy makers realise the need for investing in the health, education, and general wellbeing of the young. Our young population is at a greater risk than adults when using contraceptive services. This risk results from a lack of early education in human reproductive system as well as the cultural taboos surrounding the subject. Affordability, accessibility, and knowledge of contraception are inadequate for young women and couples who would want to space pregnancies. Individuals’ reproductive intentions remain uninformed by critical awareness that swells the number of unintended pregnancies, further aggravated by hazardous unprofessionally administered abortions. One-third of Young Married Women Have a Desire to Use Contraception There are misconceptions that family planning is for older or married women, despite the fact that many adolescent girls are sexually active. Nearly one third of the young married women, aged 15–19, have a desire to use contraception but are not currently using any contraceptive methods in Pakistan.